2018
DOI: 10.3390/min8090413
|View full text |Cite
|
Sign up to set email alerts
|

Infra Red Spectroscopy of the Regulated Asbestos Amphiboles

Abstract: Vibrational spectroscopies (Fourier Transform Infra Red, FTIR, and Raman) are exceptionally valuable tools for the identification and crystal–chemical study of fibrous minerals, and asbestos amphiboles in particular. Raman spectroscopy has been widely applied in toxicological studies and thus a large corpus of reference data on regulated species is found in the literature. However, FTIR spectroscopy has been mostly used in crystal–chemical studies and very few data are found on asbestos amphiboles. This paper … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 67 publications
2
12
0
1
Order By: Relevance
“…Non-coated amosite and crocidolite show Fe/Si ratios of 1.53 and 2.18, respectively. The reference asbestos amphiboles UICC amosite and UICC crocidolite, on the other hand, have Fe/Si ratios of 0.8 and 0.7, respectively [38]. Figure 5 displays a HRTEM image and the corresponding FFT electron diffraction patterns of a non-coated crocidolite fibre recovered from the lung tissue.…”
Section: Percentilesmentioning
confidence: 99%
“…Non-coated amosite and crocidolite show Fe/Si ratios of 1.53 and 2.18, respectively. The reference asbestos amphiboles UICC amosite and UICC crocidolite, on the other hand, have Fe/Si ratios of 0.8 and 0.7, respectively [38]. Figure 5 displays a HRTEM image and the corresponding FFT electron diffraction patterns of a non-coated crocidolite fibre recovered from the lung tissue.…”
Section: Percentilesmentioning
confidence: 99%
“…4) shows, in addition to the quadruplet of peaks observed in the powder pattern (displayed as the inset in Fig. 4), two broad absorptions at 4327 and 4194 cm −1 , which result from the combination of the stretching and libration vibrations of the O-H dipole (Della Ventura et al, 2021a).…”
Section: Ftir Spectroscopymentioning
confidence: 94%
“…Figures 3 and 4 show representative FTIR ATR spectra collected on powdered fragments of the shards. Spectrum d f has been recorded on a fiber bundle extracted from sample d. The bands, for instance, the Si-O stretching and bending modes at~960 (1015 and 1080) and 620 cm −1 (Figure 3), are characteristic of asbestos and similar compounds (amphiboles and pyroxenes) [14][15][16][17][18][19][20][21]. From this first analysis, it can be seen that the samples b and d on the one hand and the samples a and c on the other hand are rather similar, but sample d appears to be more heterogeneous.…”
Section: Evidence Of Asbestos Fibersmentioning
confidence: 99%
“…The large number of phases identified by XRPD and the variety of Raman spectra observed are consistent with a firing taking place at low temperature, with a resultant degradation of the pristine mineral occurring without the clear formation of neophases. Trittschack et al [18][19][20] observed the intensity decrease of the O-H stretching mode at~3600-3700 cm −1 over 450 • C (de-hydroxylation) and then the formation of forsterite at a temperature over~500 • C, with the characteristic doublet seen at~820-850 cm −1 .…”
Section: Heating-induced Effects and Remarks On Preparation Proceduresmentioning
confidence: 99%